Critical illness polyneuropathy and myopathy [Kri̇ti̇k hastalik poli̇nöropati̇si̇ ve mi̇yopati̇si̇] - (:unkn) unknown (My University, 2008)
Background: Critical illness polyneuropathy (CIP) and clinical illness myopathy (CIM) frequently develop in patients hospitalized in the intensive care unit for more than 1 week. The underlying disorders are usually sepsis and/or multiorgan failure or treatment with neuromuscular blocking agents and steroids. CIP and CIM present with muscle weakness, especially in extremities and respiratory muscles, and failure to wean from mechanical ventilation. While polyneuropathy is an acute axonal one, myopathy has four main types. Encephalopathy which generally occurs before CIP and/or CIM may lead to a delay in diagnosis. Close follow-up of neurological functions, performing electrophysiological and laboratory studies in early period and taking biopsies as indicated leads to correct diagnosis. Early diagnosis and a systematic differential diagnosis of CIP and CIM which are usually seen simultaneously and directly related to survival are important, so that they can be managed properly. Conclusion: The incidence of CIP and CIM may be reduced by eliminating the currently defined risk factors. Although specific therapies have not been discovered, supportive treatment, aggressive management of sepsis and elimination of contributory medications may be beneficial.
Keywords: Critical illness; Myopathy; Polyneuropathy